GE_GERICHTE P/2412/2009 vom 26. Mai 2014 - GE Cour de justice (2014)
ENQUÊTE PÉNALE; PRINCIPE DE LA CÉLÉRITÉ; GESTION DÉLOYALE; SÉQUESTRE(MESURE PROVISIONNELLE); CRÉANCE; PROPORTIONNALITÉ | CP.158; CPP.5; CPP.263